THE DZUNGAR KHANATE AND THE MANCHU EMPIRE: THE IMPACT OF TWO NOMADIC EMPIRES ON THE FORMATION OF CENTRAL ASIA’S POLITICAL BORDERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the 17th and 18th centuries, the Dzungar Khanate and the Manchu-led Qing Empire emerged as two formidable military-political powers that significantly influenced the fate of Central Asia. Their confrontation and interaction not only shaped the outcome of ethnic and political processes across the vast steppe regions, but also laid the foundation for the formation of modern borders in the region. This article examines the causes of the conflict, strategies for governing nomadic territories, and the long-term consequences of these developments for the political geography of Central Asia.
Keywords: Dzungar Khanate, Manchu Empire (Qing), Central Asia, Nomadic empires, political borders,ethno-political processes,territorial conflicts,governance of nomadic territories.